Yoga improves self-reported cognitive function among cancer survivors: results from the STAYFit trial - Gothe, Neha P.; Erlenbach, Emily; Salerno, Elizabeth A. (Frontiers in Cognition, 2024)
Various physical activity-based interventions have been tested to determine their efficacy in improving cancer related cognitive decline (CRCD), however the role of mind-body practices such as yoga remains to be explored. In this manuscript we present preliminary effects of yoga vs. aerobic and stretching-toning modalities of exercise on CRCD among adult cancer survivors. Participants (N=78) were randomized to one of the three exercise groups for a duration of 12-weeks and engaged in ≥150 min per week of supervised group exercises. At baseline and following the 12-week interventions, participants completed the Functional Assessment of Cancer Therapy–Cognitive Function. Results demonstrated a significant group*time interaction for FACT-Cog perceived cognitive abilities subscale, with participants in the yoga group demonstrating a significant increase as compared to the aerobic and stretching-toning groups. The FACT-Cog total score showed a significant time effect with all groups demonstrating a significant increase at follow-up. Other subscales did not show any significant improvements. These findings provide promising evidence for the effects of yoga on self-reported cognitive function in cancer survivors. Notably, 12-weeks of yoga showed an increase in the perceived cognitive abilities and demonstrated a clinically meaningful increase in total cognitive function as measured by the FACT-Cog, suggesting that this exercise modality has the potential to impact this important health outcome during cancer survivorship.